2005
DOI: 10.1159/000087375
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Ultrasonography of the Endometrium in Postmenopausal Japanese Women

Abstract: Aims: To determine the cut-off level of endometrial thickness for detecting endometrial disease on a large scale of screening and to examine the usefulness of transvaginal ultrasonography (TVS) for endometrial disease screening in asymptomatic postmenopausal Japanese women. Methods: The study involved 1,400 postmenopausal women in whom endometrial thickness was measured with TVS, and then compared with the histopathological diagnosis of endometrial specimens. Results: The prevalence of endometrial disease in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…However, currently routine screening for endometrial cancer is not recommended in asymptomatic women, either for the premenopausal [14] or the postmenopausal population [2,5,6]. Some of the main justifications against its utilization are the poor positive predictive value of TVUS and the low incidence of endometrial cancer in asymptomatic postmenopausal women [15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, currently routine screening for endometrial cancer is not recommended in asymptomatic women, either for the premenopausal [14] or the postmenopausal population [2,5,6]. Some of the main justifications against its utilization are the poor positive predictive value of TVUS and the low incidence of endometrial cancer in asymptomatic postmenopausal women [15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…Even with 52.7% of these patients (78/148) currently taking tamoxifen or HRT, there was only a single case of each complex atypical hyperplasia (0.7%) and endometrial cancer (0.7%) [16]. In a study published in this journal, Tsuda et al [17] screened 1,400 postmenopausal Japanese women not taking HRT by TVUS and endometrial cytology sampling, of which 883 (63.1%) were asymptomatic. Endometrial pathology, ranging from simple hyperplasia to endometrial cancer, was detected in 2.3% (20/883) and the probability of missing a pathological diagnosis was 0.004 if the ET was ≤4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There is no unanimous agreement regarding the endometrial thickness that have to be considered pathologic. [13][14][15][16][17][18] The endometrial thickness physiologically changes in relation to the age and, in cyclic women, to the endometrial phase. The administration of hormonal therapy may also influence the endometrial thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Thickened endometrium as evaluated by TVS may be the consequence of many pathological and nonpathological conditions different from carcinoma or hyperplasia such as endometrial polyps or cystic endometrium, which is typically induced by tamoxifen. [13][14][15][16][17][18] Often, TVS does not provide a definitive diagnoses particularly due to its high false-positive rate. A recent meta-analysis of the diagnostic accuracy of endometrial thickness measurements by transvaginal or transabdominal ultrasound involving 9,031 women with postmenopausal bleeding reported that using a 5 mm cut-off level, a positive test raised the probability of carcinoma from 14.0% to 31.3%, while a negative test reduced it to 2.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation